Mediating Role of Time Pressure on the Relationship between Organizational Psychology Safety and Motivation of Learning from Failure in Large-Scale Construction Project - Lingna Lin; Xiaowei Luo; Sainan Cheng; Min Xu; Lianbo Zhu (Advances in Civil Engineering)
Large-scale construction projects are characterized by the temporary cooperation of different parties with objectives, making it challenging to learn from failure under great time pressures. Learning from failure in such multiparties projects must overcome the fear of speaking out the “failure,” reflected by organizational psychology safety. This study aims to explore the impact of organizational psychology safety on the motivation of learning from failure under the mediating role of time pressure by a cross-sectional study. Data was collected by a questionnaire survey of 189 construction practitioners and analyzed by applying regression analysis. Results show that organizational psychology safety was negatively associated with time pressure and positively with the motivation of learning from failure. Time pressure was detrimental to the motivation of learning from failure, and it partially mediated the relationship between organizational psychology safety and motivation of learning from failure. Insights from the analysis could help the managers of organizations or projects to attach importance to the influence and role of learning from failure and could provide them with guides to implement lessons-learned systems.